Lengthy one-dimensional magnetite (Fe3O4) sub-microfibers with excellent electrochemical performance - Ma, J.; Chang, J.; Ma, H.; Zhang, D.; Ma, Q.; Wang, Shaobin (Academic Press, 2017)
© 2017One dimensional Fe3O4 sub-microfibers with an average diameter of about 920 nm and length of about 25 µm were prepared by hydrothermal synthesis in the presence of sodium citrate (Na3cit). The physicochemical properties were characterized by X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), and scanning electron microscopy (SEM). It was found that Fe3O4 crystal nuclei were generated from different Fe2+-citrate complexes under hydrothermal conditions and Na3cit as a capping agent promoted the formation of Fe3O4 microfibers. The Fe3O4 nanocrystals grew along the (1 1 0) axis on the exposed (1 1 1) facet, and then further formed microfibers via an oriented attachment mechanism during the collisions. Polyvinylpyrrolidine (PVP) was more conducive to microfibers growth in comparison to polyethyleneglycol 4000 (PEG-4000), cetyltrimethylammonium bromide (CTAB) and sodium dodecyl sulfate (SDS). The electrochemical measurements show that the Fe3O4 sub-microfibers had a specific capacitance of 117.6 F g-1 with good cycling performance.